2010
DOI: 10.1021/om100049n
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Complexes of the Heterodiphosphineo-C6H4(CH2PtBu2)(CH2PPh2) Are Highly Selective and Robust Catalysts for the Hydromethoxycarbonylation of Ethene

Abstract: The coordination chemistry and ethene hydromethoxycarbonylation catalysis with the diphosphine o-C 6 H 4 (CH 2 P t Bu 2 )(CH 2 PPh 2 ) (L 3 ) is reported and the results compared with the analogous chemistry of the symmetrical diphosphines o-C 6 H 4 (CH 2 P t Bu 2 ) 2 (L 1 ) and o-C 6 H 4 (CH 2 PPh 2 ) 2 (L 2 ). Palladium-catalyzed ethene hydromethoxycarbonylation studies under the commercial catalytic conditions are reported. The results obtained using L 1-3 as supporting ligands show that the catalysts deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 76 publications
(53 reference statements)
2
39
0
Order By: Relevance
“…These results can be compared with those obtained by Pringle20a et al. by using ligands A , Q , and R (Figure 4) for the methoxycarbonylation of ethylene.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…These results can be compared with those obtained by Pringle20a et al. by using ligands A , Q , and R (Figure 4) for the methoxycarbonylation of ethylene.…”
Section: Methodsmentioning
confidence: 63%
“…The first two were very active for the production of methyl propionate, and the latter resulted in a sluggish reaction rate and afforded ethene/CO co‐oligomers and polyketone 10j. 20 Notably, the Pd catalyst based on ligand Q had a longer lifetime than the Pd complex derived from ligand A 20a. This is another demonstration that both steric and electronic properties of the ligand are important.…”
Section: Methodsmentioning
confidence: 98%
“…111 The field of hydro/methoxycarbonylation of ethylene to methyl propanoate using BTDPMB-based systems and variations of the ligand has been recently reviewed by Fanjul and co-workers. [112][113][114] Drent and Jager have shown the BTDPMB/palladium system to give methyl pentanoate from 2-butene in 97% selectivity at 65 bar and 100℃, 115 showing the methoxycarbonylation of a carbon chain longer than ethylene was possible. The same authors desired to increase the selectivity to the linear ester and found that using a mixture anisole/methanol : 2/1 as a solvent for the methoxycarbonylation of 2-butene and 1-octene yielded a full conversion to the ester with high selectivity to the linear species (97%).…”
Section: The Alkoxycarbonylation Of Simple Alkenesmentioning
confidence: 99%
“…Table 2. S2) match well with those of an analogous molecule containing a diphosphanylamine ligand moiety. [11] The mononuclear form of 1 in powdered bulk samples as well as in solution has been established by different experimental techniques. The 31 P NMR spectrum of L in CDCl 3 exhibits two signals at 60.60 and -21.8 ppm corresponding to P1/P2 and P3, respectively ( Figure S2a) Figure S2b).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%